PATHOGENESIS AND MODERN THERAPEUTIC STRATEGIES IN RHEUMATOID ARTHRITIS - S. B. Parpieva; E. A.Vasilevsky; O.T.Dadabaev; N. G. Kamalov (The Conference Hub, 2025)
Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disease that primarily manifests as a persistent inflammatory synovitis, leading to progressive cartilage damage and bone erosion if left undertreated [6]. Affecting up to 1% of the global population, RA imposes a substantial burden on individuals and healthcare systems, often causing significant pain, functional disability, and a diminished quality of life [6]. The last two decades have witnessed a revolutionary shift in the management of RA.